Evaluation of the Use of Interactive Flat Panel (IFP) as a 21st-Century Learning Innovation in Elementary Schools of Sleman Regency - Ahyar Nasukha; Akbar Al Masjid; Ardian Arief (Bulletin of Educational Management and Innovation, 2025)
Background: The 21st-century educational transformation demands a paradigm shift toward interactive, collaborative, and student-centered digital ecosystems. In response, the government distributed Interactive Flat Panel (IFP) media to elementary schools in Sleman Regency in December 2025 to boost instructional quality. However, post-distribution data indicates a prominent phenomenon where many schools and teachers have not yet optimally integrated this advanced technology into their daily learning processes. Purpose: This study specifically aims to evaluate the effectiveness and usage patterns of IFP media as a 21st-century learning innovation in elementary schools across Sleman Regency. Additionally, it identifies the supporting and inhibiting factors influencing implementation based on curricular artifacts and documentary evidence to guide future strategic policy directions and teacher mentoring programs. Method: This evaluative-empirical field research applied a mixed-methods approach. From 556 initial responses, data screening yielded 438 clean datasets, with link validation isolating 353 fully accessible cloud links and 85 restricted links. A micro-level content analysis was then conducted on a stratified random sample of 34 Lesson Plans using a Content Analysis Checklist Sheet, synthesizing descriptive quantitative and qualitative analysis streams through method triangulation. Findings: The findings reveal a clear gap between high administrative reporting compliance and the depth of actual classroom technology integration. At the macro level, 19.41% of documents face first-order barriers due to locked cloud storage permissions. At the micro level, explicit instructional planning for IFP reached only 35.3% and is heavily dominated by teacher-centered, one-way patterns that relegate the device to the mere substitution level of the SAMR model.